Acidic Barren Slope Profiling using Electrical Resistivity Imaging (ERI) at Ayer Hitam area Johor, Malaysia. (April 2016) - Azhar, A T S; Hazreek, Z A M; Aziman, M; Haimi, D S; Hafiz, Z M
Abstract: Recently, non-destructive method such as the electrical resistivity technique has become increasingly popular in engineering, environmental, mining and archeological studies nowadays. This method was popular in subsurface profiling due to its ability to replicate the images of the subsurface indirectly. The soil slope found in Batu Pahat, specifically in Ayer Hitam, is known to be problematic due to its barren condition. This location is believed to contain futile soil due to its difficulty in supporting the growth of vegetations. In the past, acidic barren slope assessment using non-destructive method was rarely being used due to several reasons related to the equipment and knowledge constraints. Hence, this study performed an electrical resistivity imaging using ABEM Terrameter LS in order to investigate the acidic barren slope conditions. Field data acquisition was based on Schlumberger and Wenner arrays while RES2DINV software was used to analyze and generate a 2-D model of the problematic subsurface profile. Based on electrical resistivity results, it was found that the acidic barren slope studied consists of two main zones representing residual soil (electrical resistivity value = 10 - 600 Ωm) and shale (electrical resistivity value = 20 - 2000 Ωm). The results of resistivity value were correlated with the physical mapping and the in situ mackintosh probe test for verification purposes. It was found that the maximum depth of the mackintosh probe test was 1.8 m due to its ground penetration limitation. However, the results of the resistivity section managed to achieve greater depth up to 40 m. Hence, the correlation between electrical resistivity and mackintosh probe results can only be performed at certain depth of the acidic barren slope profile in contrast with the physical mapping which able to define the whole section of the barren soil slope structure. Finally, a good match of electrical resistivity results calibrated with mackintosh and physical mapping data showed that this technique was appropriate to be applied in near-surface acidic barren slope assessment which can further compliment borehole data and other physical mapping data at a lower cost, higher speed, large data coverage and better environmental sustainability.